No news is good news: what you see and what you don't get to see / Syed Alwi Shahab - Shahab, Syed Alwi (Centre for Media and Information Warfare Studies, 2008)
Spreading the truth is certainly not the first commitment of the news system. The news is supposed to tell us accurately about the world beyond our view, but what it does is to give a distorted account of the world beyond our view. Why is this the case? Why is truth least uppermost in the selection of news stories? What kind of warp is there to the news? What does the circulation of this sort of material do for the society it is supposed to serve and inform? What is the real function of the news? This paper will explore and discuss such questions.